Post-traumatic stress disorder among LGBTQ people: a systematic review and meta-analysis - Mattia Marchi; Antonio Travascio; Daniele Uberti; Edoardo De Micheli; Pietro Grenzi; Elisa Arcolin; Luca Pingani; Silvia Ferrari; Gian M. Galeazzi (Cambridge University Press, 2023)
Abstract Aims Lesbian, gay, bisexual, transgender and queer people (LGBTQ) are at increased risk of traumatization. This systematic review aimed to summarize data regarding the risk of post-traumatic stress disorder (PTSD) for LGBTQ people and their subgroups. Methods Medline, Scopus, PsycINFO and EMBASE were searched until September 2022. Studies reporting a comparative estimation of PTSD among LGBTQ population and the general population (i.e., heterosexual/cisgender), without restrictions on participants' age and setting for the enrolment, were identified. Meta-analyses were based on odds ratio (OR and 95% confidence intervals [CI]), estimated through inverse variance models with random effects. Results The review process led to the selection of 27 studies, involving a total of 31,903 LGBTQ people and 273,842 controls, which were included in the quantitative synthesis. Overall, LGBTQ people showed an increased risk of PTSD (OR: 2.20 [95% CI: 1.85; 2.60]), although there was evidence of marked heterogeneity in the estimate (I2 = 91%). Among LGBTQ subgroups, transgender people showed the highest risk of PTSD (OR: 2.52 [95% CI: 2.22; 2.87]) followed by bisexual people (OR: 2.44 [95% CI: 1.05; 5.66]), although these comparisons are limited by the lack of data for other sexual and gender minorities, such as intersex people. Interestingly, the risk of PTSD for bisexual people was confirmed also considering lesbian and gay as control group (OR: 1.44 [95% CI: 1.07; 1.93]). The quality of the evidence was low. Conclusions LGBTQ people are at higher risk of PTSD compared with their cisgender/heterosexual peers. This evidence may contribute to the public awareness on LGBTQ mental health needs and suggest supportive strategies as well as preventive interventions (e.g., supportive programs, counselling, and destigmatizing efforts) as parts of a tailored health-care planning aimed to reduce psychiatric morbidity in this at-risk population.